Oracle database programming using Java and Web services - Mensah, Kuassi (Amsterdam ; Boston : Elsevier Digital Press, 2006)
The traditional division of labor between the database (which only stores and manages SQL and XML data for fast, easy data search and retrieval) and the application server (which runs application or business logic, and presentation logic) is obsolete. Although the books primary focus is on programming the Oracle Database, the concepts and techniques provided apply to most RDBMS that support Java including Oracle, DB2, Sybase, MySQL, and PostgreSQL. This is the first book to cover new Java, JDBC, SQLJ, JPublisher and Web Services features in Oracle Database 10g Release 2 (the coverage starts with Oracle 9i Release 2). This book is a must-read for database developers audience (DBAs, database applications developers, data architects), Java developers (JDBC, SQLJ, J2EE, and OR Mapping frameworks), and to the emerging Web Services assemblers. * Describes pragmatic solutions, advanced database applications, as well as provision of a wealth of code samples * Addresses programming models which run within the database as well as programming models which run in middle-tier or client-tier against the database. * Discusses languages for stored procedures: when to use proprietary languages such as PL/SQL and when to use standard languages such as Java; also running non-Java scripting languages in the database * Describes the Java runtime in the Oracle database 10g (i.e., OracleJVM), its architecture, memory management, security management, threading, Java execution, the Native Compiler (i.e., NCOMP), how to make Java known to SQL and PL/SQL, data types mapping, how to call-out to external Web components, EJB components, ERP frameworks, and external databases. * Describes JDBC programming and the new Oracle JDBC 10g features, its advanced connection services (pooling, failover, load-balancing, and the fast database event notification mechanism) for clustered databases (RAC) in Grid environments. * Describes SQLJ programming and the latest Oracle SQLJ 10g features, contrasting it with JDBC * Describes the latest Database Web services features, Web services concepts and Services Oriented Architecture (SOA) for DBA, the database as Web services provider and the database as Web services consumer. * Abridged coverage of JPublisher 10g, a versatile complement to JDBC, SQLJ and Database Web Services.
pt. 1. Java in the database -- pt. 2. Java persistence and Java SQL data access -- pt. 3. Oracle database programming with SQLJ -- pt. 4. Oracle database programming with JPublisher -- pt. 5. Programming the Oracle database with web services -- pt. 6. Putting everything together -- Index.
Includes bibliographical references and index.
Keywords: Oracle (Computer file); Java (Computer program language).; Web services; Electronic books